Eagle syndrome masquerading as a chicken bone - Jason E. Cohn; Sammy Othman; Karima Sajadi-Ernazarova (International Journal of Emergency Medicine, 2020)
Abstract This is a brief report of a 17-year-old male who presented to the emergency department with odynophagia and a foreign body sensation in the throat after choking on a chicken wing. A soft tissue neck radiograph was performed which revealed a 4.6-cm linear object in the vallecula read by the radiology department as a chicken bone. The otolaryngology team was consulted and performed a nasopharyngeal laryngoscopy which did not reveal a foreign body in the upper aerodigestive tract. On physical examination, the right tonsillar fossa was tender to palpation. Upon further review of the radiograph, the right stylohyoid ligament was noted to be elongated and calcified. Thereafter, the diagnosis of Eagle syndrome was made. This case provides an important teaching point for providers by pointing out a syndrome that can mimic other disease processes. In addition, it emphasizes the importance of providers reviewing their own films.